A phase 1 study to evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of danuglipron (PF‐06882961), an oral small‐molecule glucagon‐like peptide‐1 receptor agonist, in Japanese adults with type 2 diabetes mellitus. Issue 3 (19th December 2022) - Ono, Ryosuke; Furihata, Kenichi; Ichikawa, Yoshihiko; Nakazuru, Yoshiomi; Bergman, Arthur; Gorman, Donal N.; Saxena, Aditi R.
Abstract: Aims: This study investigated the safety, tolerability, pharmacokinetics and pharmacodynamics of danuglipron (PF‐06882961), which is a novel, oral small‐molecule glucagon‐like peptide‐1 receptor agonist, in Japanese participants with type 2 diabetes mellitus (T2DM). Materials and Methods: This phase 1, randomized, double‐blind, placebo‐controlled, parallel‐group study enrolled adult Japanese participants with T2DM inadequately controlled on diet and exercise. Participants received twice‐daily oral doses of placebo or multiple ascending doses of danuglipron titrated to 40, 80 or 120 mg twice daily over 8 weeks. The primary outcome was the safety and tolerability of danuglipron. Secondary and exploratory outcomes included plasma pharmacokinetics, glycaemic parameters and body weight. Results: In the 37 participants randomized, the most common treatment‐emergent adverse events were nausea, vomiting, abdominal discomfort, diarrhoea and headache. Most treatment‐emergent adverse events were of mild or moderate intensity. Dose‐proportional increases in danuglipron exposure parameters were observed at steady state (Day 56). Significant reductions from baseline were observed with danuglipron on Day 56 for mean daily glucose [least squares mean (90% confidence interval) placebo‐adjusted difference of up to −67.89 (−88.98, −46.79) mg/dl] and on Day 57 for fasting plasma glucose [up to −40.87 (−53.77, −27.98) mg/dl], glycated haemoglobin [up to −1.41% (−2.01%, −0.82%)] and body weight [up to −1.87 (−3.58, −0.17) kg]. Conclusions: In Japanese adults with T2DM, danuglipron exhibited dose‐proportional increases in plasma exposure at steady state and robustly reduced glycaemic parameters and body weight after 8 weeks of dosing, with a safety profile consistent with the mechanism of action.